The Effect of Equivalent Rate and Return on Assets on Asset Growth at BPRS Puduarta Insani - Ira Fransiska; Atika Atika; Nurwani Nurwani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research aims to analyze the influence of Equivalent Rate and Return On Asset (ROA) on asset growth at the Sharia People's Credit Bank (BPRS) Puduarta Insani. The method used in this study is multiple linear regression analysis to examine the relationship between independent and dependent variables. The results indicate that the Equivalent Rate has a significant positive effect on the asset growth of BPRS, with a significance value (sig-t) of 0.045, which is less than 0.05. This indicates that an increase in the Equivalent Rate will be followed by an increase in asset growth. On the other hand, ROA shows a positive but insignificant relationship with asset growth, with a significance value (sig-t) of 0.687, which is greater than 0.05. These findings emphasize the importance of managing the Equivalent Rate in driving asset growth for BPRS, while ROA cannot be considered a primary indicator in this context. This research contributes to BPRS management in formulating more effective strategies to enhance asset performance.